PISA: a political project and a research agenda. Issue 1 (2nd January 2022) - Sjøberg, Svein; Jenkins, Edgar
ABSTRACT: PISA (Programme for International Student Assessment) is one of two large scale international comparative projects of student assessment that now exert considerable influence upon school science education policy, the other being TIMSS (Trends in International Mathematics and Science Study). This paper focuses on PISA, now the most influential study. This article outlines the origins of PISA, identifies some of the challenges in its construction and the claims made for it. It argues that while the statistical and methodological aspects of PISA have received much research attention, other elements of PISA have been largely ignored. In particular, there are several outcomes of PISA testing that point towards a significant research agenda. In addition, the political, ideological and economic assumptions underpinning the PISA project have implications for school science curriculum policy that deserve closer scrutiny and debate.